Securing Chaos - Karlsson, Robin (My University, 2016)
Wireless Sensor Network (WSN) is a field on the rise with the advent of Internet of Things (IoT), where small and cheap computers are distributed to collect information about their local environment. To ensure resistance against malevolent adversaries, and ultimately correct functionality, security is commonly used. Chaos [23] is a novel network primitive with built-in high performance all-to-all data sharing that is designed for use in WSNs. This thesis investigates how to secure Chaos from the ground up. As part of this thesis, we add a link layer security layer to the existing network, and design and implement a protocol based on Elliptic Curve Diffie-Hellman Ephemeral (ECDHE) for securely enabling new motes to join. This Elliptic Curve Cryptography (ECC) based approach enables flexible extensions in future iterations. We show that our dynamic join protocol performs sufficiently well for Chaos, such as being able to build a complete network of 32 motes from a single mote in less than 18 minutes on the TelosB platform, and that the approach is viable despite the high limitations of the Chaos protocol and the TelosB motes.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science